PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN DANA OTONOMI KHUSUS TERHADAP TINGKAT KEMISKINAN DI PROVINSI ACEH PERIODE 2010-2017 - Muhammad Kadafi; Murtala Murtala (LPPM UNIMAL, 2020)
This study aims to analyze the Effect of Local original Revenue, General Allocation Funds and Special Autonomy Funds on Poverty Rates in Aceh Province 2010-2017. The data used in this study are panel data from 2010 to 2017. This research model uses panel data regression. Results of the study Partially the local original revenue and the special autonomy fund did not affect poverty in the Aceh Provincial Government, the general allocation fund affected the poverty in the Aceh Provincial Government. Simultaneously, local original revenue, general allocation funds and special autonomy funds affect poverty in the Aceh Provincial Government.Keywords: Local Revenue, General Allocation Fund, Special Autonomy Fund, Poverty Rate